A jejunal atresia type I in newborn: a case report - Anak Agung Adi Suryaningrat; Kadek Deddy Ariyanta (DiscoverSys Inc., 2020)
Background: Intestinal atresia is a common cause of neonatal intestinal obstruction. Jejunal atresia occurs more frequently than duodenal or colonic atresias, while single atresias are most commonly encountered. This case report aims to evaluate the recent management of jejunal atresia type I in newborn.Case Description: We report one case of jejunal atresia types I. A 8-days old newborn was born with signs of upper gastrointestinal obstruction. Bile-stained vomiting was reported on the third day of life. Postnatal abdominal X-ray showed the triple bubble sign. Laparotomy was performed at 9th days of life when it revealed the type of jejunal atresia type 1. The resection procedure on the atresia, such as tapering and end to end anastomosis, was performed. Laparotomy revealed the type I Jejuno-ileal atresia 20 cm from Treitz ligament then resection on the atresias, tapering, and end to end anastomosis was performed. Post-operative, the baby was admitted to NICU with total parenteral nutrition and continued antibiotics due to sepsis.Conclusion: The case was referred to the neonatal intensive care unit post-surgery with a carefully monitored fluid balance, temperature, and sign of sepsis. A definitive antibiotic was given due to sepsis, as well as total parenteral nutrition.Â